2019
DOI: 10.1038/s41598-019-49648-2
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke alters the transcriptome of non-involved lung tissue in lung adenocarcinoma patients

Abstract: Alterations in the gene expression of organs in contact with the environment may signal exposure to toxins. To identify genes in lung tissue whose expression levels are altered by cigarette smoking, we compared the transcriptomes of lung tissue between 118 ever smokers and 58 never smokers. In all cases, the tissue studied was non-involved lung tissue obtained at lobectomy from patients with lung adenocarcinoma. Of the 17,097 genes analyzed, 357 were differentially expressed between ever smokers and never smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…may explain the differences. Since it has been demonstrated that cigarette smoking alters the transcription level of many genes in normal lung cells of LUAD, although only seven genes up-regulated in all studies (Pintarelli et al, 2019), our results can extend the same conclusion to the RE transcriptome. Irrespective of the rationale for these differences, the 30 differentially expressed REs in normal cells cannot be considered lung biomarkers.…”
Section: Discussionsupporting
confidence: 84%
“…may explain the differences. Since it has been demonstrated that cigarette smoking alters the transcription level of many genes in normal lung cells of LUAD, although only seven genes up-regulated in all studies (Pintarelli et al, 2019), our results can extend the same conclusion to the RE transcriptome. Irrespective of the rationale for these differences, the 30 differentially expressed REs in normal cells cannot be considered lung biomarkers.…”
Section: Discussionsupporting
confidence: 84%
“…MGLL knock-out mice exhibited a higher incidence of neoplasia in lung [ 31 ]. MYO1A (Myosin I a) expression was higher in ever smokers than in never smokers [ 33 ]. MYO1A had mutations and promoter hypermethylation in patients with colorectal cancer and gastric tumors; therefore, lower levels of MYO1A expression was associated with faster tumor progress and poor prognosis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proven by previous studies, the probability of NSCLC in long-term heavy smokers is 10–20 times higher than that in non-smokers, and the younger the age at which smokers begin to smoke, the higher the risk of NSCLC. [ 11 , 12 ] Furthermore, smoking not only directly affects personal health, but also has a negative impact on the health of the surrounding population, leading to a significant increase in the incidence of NSCLC among passive smokers. [ 13 , 14 ] The incidence of NSCLC in urban residents is higher than that in rural areas, which may be related to urban air pollution and the carcinogens contained in smoke and dust.…”
Section: Discussionmentioning
confidence: 99%